The impact of barley straw conditioning on the inhibition of Scenedesmus using chemostats - Murray, Daniel; Parsons, Simon A.; Jarvis, Peter; Jefferson, Bruce (Elsevier Science B.V., Amsterdam., 2010)
The current paper investigates the role of barley straw conditioning on inhibiting the alga Scenedesmus. Fresh, pre-rotted and white rot fungi (WRF) augmented straw was tested in a series of chemostat experiments over 15 weeks. All three systems were effective at inhibiting the alga with differences observed in the lag time before inhibition occurred and the rate of alga decline. Lag times of 8, 4 and 1 week(s) were recorded for the fresh, rotted and fungi-treated straws, respectively, with a maximum inhibition rate of >7 x 10(4) cells week (1) observed for the fungi pre-treated system. Overall, the results indicate that pre-treatment is a viable method to enable barley straw to be used in a more reactive manner. Explanation is postulated that during pre-treatment no alternative sources of nitrogen are available, thereby leading to greater bacterial decomposition of straw lignin to release inhibitory substances. The principle of utilising an engineered pre-treatment by inoculating barley straw with WRF to enhance the impact of the straw on algal inhibition has been clearly demonstrated. Further work is required to understand how the straw pre-treatment stage can be reduced to minimise its duration while maximising the inhibitory effect of adding barley straw. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Algal control Barely straw Chemostat Scenedesmus hordeum-vulgare algal growth lignin wood decomposition reservoir liquid fungi decay water